Perbandingan Linguistik Historis Bahasa Dayak Ngaju dan Bakumpai: Implikasi terhadap Pelestarian Bahasa dan Budaya Kalimantan: Historical Linguistic Comparison of Ngaju and Bakumpai Dayak Languages: Implications for the Preservation of Kalimantan Languages and Culture - Hasby, Nazar; Qalyubi, Imam; Misrita, Misrita; Kodriyah, Lailatul; Angrum, Alna Triskaya; Noor, Pajrian (Information Technology and Science(ITScience), 2025)
This study compares the Dayak Ngaju and Bakumpai languages from a historical linguistic perspective to reveal their kinship and phonetic changes that occur. Although they come from the same language family, these two languages show phonological differences due to social, cultural, and contact influences with Banjar Malay and Indonesian. This poses a threat to the sustainability of the Bakumpai language. This study uses a comparative historical linguistic approach with lexicostatistical analysis to measure the level of kinship between the Dayak Ngaju and Bakumpai languages. The data used is basic Swadesh vocabulary consisting of 200 words. In addition, phonetic changes such as apheresis, apocope, and syncope are analysed to identify phonetic change patterns in both languages. The analysis results show that the level of kinship between the Dayak Ngaju and Bakumpai languages reaches 80.5%, indicating the closeness of the two in one language family. Phonetic changes, such as initial (afteresis) and final (apocope) sound deletion, are found in both languages, reflecting phonological evolution influenced by social and cultural factors. This study concludes that despite phonetic differences, the Dayak Ngaju and Bakumpai languages still share significant similarities, indicating a strong kinship. These findings reinforce the importance of preserving the endangered Bakumpai language and contribute to local Kalimantan culture's linguistic understanding and preservation.